Effect of grain structure on the mechanical properties of a Monel alloy fabricated by laser-based directed energy deposition - Chen, Ze (2023)
Monel K-500 is a Ni–Cu alloy widely used in the marine and offshore industry due to their superior resistance to corrosion in seawater and hence easily degraded. To address this problem, laser-based directed energy deposition (LDED) is used to repair or refabricate these high-value worn parts. To optimize the mechanical properties of repaired parts, the commonly applied solution and aging is not ideal because it also changes the properties of the base materials. Consequently, in situ control of the grain structures during the LDED process becomes an effective approach for high-performance repair. In this study, we fabricated a duplex grain structure with small grain size and low texture intensity using low laser power and scanning velocity. The duplex microstructure consists of short columnar grains and zigzag-distributed fine equiaxed grains. The formation of this grain structure is dependent on both the solidification and recrystallization mechanisms. The strength of this grain structure is improved to 523.5 MPa without the sacrifice of ductility, which is instead 20% higher than that of the counterpart consisting of typical columnar grains due to the grain refinement and crack toughening. The mechanical properties of the alloy with the duplex grain structure are even comparable to heat-treated Monel K-500 fabricated by wire arc additive manufacturing. This work provides valuable insights into the in situ optimization of the microstructure and mechanical properties of LDED-fabricated parts.